An Intriguing Multinuclear Cluster Based on Zinc and Benzotriazole Under Solvothermal Synthesis - Xie, Si-Cai (Asian Journal of Chemistry, 2013)
The intriguing multinuclear cluster [compound 1, Zn9(btz)12(CH3COO)6, btz = benzotriazole] was obtained by solvothermal reactions using zinc(II) nitrate and benzotriazole and its crystal structure was solved from conventional single-crystal X-ray data. Crystal data for compound Zn9(btz)12(CH3COO)6: triclinic space group P-1, a = 13.0714(4) Å, b = 14.0576(4) Å, c = 16.0683(5) Å, a = 69.265(3)º, b = 78.194(2)º, g = 65.436(3)º, V = 2505.71(13) Å3 and Z = 1.